The debate on the economic effects of minimum wage legislation - Santos Miguel Ruesga-Benito; Fernando Ignacio Gonzaĺez-Laxe; Jose Picatoste (European Journal of Government and Economics (EJGE), 2017)
The minimum wage establishment has its origin in the first third of the last century. Since its creation has been a focus of continuing controversy and an unfinished debate on economics field. This work reviews the effects of the minimum wage on employment and other macroeconomic variables, from both theoretical and empirical perspectives. The method is based on the revision of the literature and the main economic indicators. The central contribution of this paper is providing a general reflection on theoretical and empirical analysis about the debate on minimum wage and its effects. The results showed that some labor policies are taking account the effects of austerity strategies, shifting the attention towards the implementation of minimum wages or their updating, in order to reduce the growing inequalities in the distribution of income, and even poverty levels.
Keywords: 330; political economy; minimum wage; employment; economic inequality